2018
DOI: 10.4236/jbm.2018.611003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geographic Location and Age on Levels of Some Biochemical Parameters of Ewes in Southern of Iraq

Abstract: A total of one hundred and ten healthy dry ewes of Arabi sheep diffusive in three geographic locations in the north of Basrah (AL-Qurna, Al-Midaina and Al-Uazair) were divided into three different age groups: <1 year old, between 1-3 years old and >3 years old, to investigate the influence of geographic location and age on the concentration of some biochemical parameters of sheep in the south of Iraq. The results showed significant (P < 0.05) changes among geographic locations in some biochemical parameters su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
5
4
0
Order By: Relevance
“…At least one study has reported no significant variation in glucose or cholesterol levels of ewes with different BCS [49], but those results are difficult to compare with ours, since they are based on samples taken from ewes after mating as well as in late pregnancy. When interpreting our results and comparing them with those from other studies, it is important to keep in mind that most of our sheep had appropriate BCS throughout the observation period, with a mean BCS-1 of 2.56 ± 0.44, a mean BCS-2 of 2.69 ± 0.52, and a mean BCS-3 = 2.45 ± 0.46, which likely explains why plasma lipid concentrations were always within physiological levels [37,47].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…At least one study has reported no significant variation in glucose or cholesterol levels of ewes with different BCS [49], but those results are difficult to compare with ours, since they are based on samples taken from ewes after mating as well as in late pregnancy. When interpreting our results and comparing them with those from other studies, it is important to keep in mind that most of our sheep had appropriate BCS throughout the observation period, with a mean BCS-1 of 2.56 ± 0.44, a mean BCS-2 of 2.69 ± 0.52, and a mean BCS-3 = 2.45 ± 0.46, which likely explains why plasma lipid concentrations were always within physiological levels [37,47].…”
Section: Discussionsupporting
confidence: 56%
“…This may mean that fatter maiden animals did not regulate glucose levels as well as thinner maiden sheep. Nevertheless, glucose levels in all animals in our study were within the physiological range for sheep (32.42–79.99 mg/dl) [34,35,36,37]. This suggests that nutritional management on the study farm was appropriate.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Samaradzija et al 2011showed that blood serum mineral concentrations such as Ca, P, Na, K, Cl and Mg are effected by the goat breeds. The values of phosphorous, Fe, copper and zinc were within normal range in Arabi and Najdi sheep (Kassim and AL-Hellou 2018;Kassim 2017).…”
Section: Resultsmentioning
confidence: 61%
“…Many factors may influence the hematological and biochemical blood parameters, these factors divide into two kinds: 1) genetic factors including genotype and breed. 2): environmental factors, including age, sex, species, season, nutrition, geographic location and physiological status (Kassim and AL-Hellou 2018;Onasanya et al 2015;Njidda et al 2014;Prisacaru 2014;Yokus et al 2006;Nazifi et al 2003).…”
Section: Introductionmentioning
confidence: 99%